Peace Based on Buddhist Philosophy - Sodachai, Phramaha Somjai Panyathepo (Journal of Dhamma for Life, 2022)
This article aims to study peace according to Buddhist philosophy. Starting from the meaning of peace, which means the happiness that comes from peace. As the Buddhist proverb says, Natthi Santiparam Sukham. There is no other happiness than peace. When categorizing the types of peace according to Buddhist philosophy Peace can be divided into two main principles: 1) worldly peace is the happiness that is the nature of the world of happiness that depends on the world is the happiness that is related to the world and the world. 2) Peaceful world. It is the happiness that is intrinsic to the mind that arises from the practice of wisdom, which is peace. Peace is essential in such a way that it brings comfort, calmness, and calmness. It is the happiness that arises from a state of calm and can progress to freedom from all factors. That is called Boromsuk have a goal that causes the cold It is blissful, clean and peaceful. It is a joy that has no ambition to benefit all others involved. It is the development of the mind towards the freedom of enlightenment, which is the supreme principle in Buddhist philosophy. In terms of how to practice or live in order to reach the goal, namely the various levels of peace, the Buddha has taught at all levels and included in the Thrisikkha, which is the need for further study and training of body, speech, mind, and wisdom until attaining peace. The highest one is Nirvana.